Penerapan Metode Eksperimen Untuk Meningkatkan Motivasi Belajar Ipa Tentang Energi Panas Pada Siswa Kelas IV Semester II SDN Cebolek 01 Margoyoso Pati - Kurniawan, Eko, Drs. Saring Marsudi, SH. M.Pd (2015)
The purpose of research is to improve students' motivation fourth grade to teaching science to the material thermal energy by using the experimental method in SDN Cebolek 01 Margoyoso Starch ". Methods of research, where research on SDN Cebolek 01 Margoyoso Margoyoso District of Pati regency. When the study from February to March 2015. The research type of classroom action research. The key outcomes of research students play an active role in the learning using the experimental method as much as 80% of students scored at or above the KKM as much as 80%. In conclusion, the experimental method can increase students' motivation in science teaching in primary schools cebolek 01 Margoyoso Pati regency. By using the experimental method, students become more active during the process of learning science. The use of the experimental method can make students more focused on learning, understanding the material of the energy source so that the learning outcomes as expected